Ocular microvascular alteration in Sjögren’s syndrome treated with hydroxychloroquine: an OCTA clinical study - Chao Yu; Jie Zou; Qian-Min Ge; Xu-Lin Liao; Yi-Cong Pan; Jie-Li Wu; Ting Su; Li-Juan Zhang; Rong-Bin Liang; Yi Shao (Therapeutic Advances in Chronic Disease, 2023)
Background: Sjögren’s syndrome (SjS) is a rare autoimmune disease, and despite our knowledge of SjS, we still lack effective treatments. Chloroquine drugs used to treat autoimmune diseases are still the primary medicine for SjS but increase the risk of chloroquine retinopathy. Objectives: The objective of this study is to use Optical Coherence Tomography Angiography (OCTA) images to monitor the microvascular changes in the fundus of SjS patients after hydroxychloroquine (HCQ) treatment and the feasibility of using them as diagnostic indicators. Design: This is a retrospective observational cohort study. Methods: Twelve healthy controls (HCs group; 24 eyes), 12 SjS patients (SjS group; 24 eyes), and 12 SjS patients treated with HCQ (HCQ group; 24 eyes) were recruited. Three-dimensional OCTA images of the retina were collected, and microvascular density was calculated for each eye. OCTA image segmentation for analysis was conducted using the central wheel division method (C1–C6), hemisphere segmentation method (SR, SL, IL, and IR), and the early treatment of diabetic retinopathy study method (ETDRS) (R, S, L, and I). Results: Retinal microvascular density was significantly lower in the SjS patients compared to the HCs group ( p  < 0.05) and much lower in the HCQ group compared to the SjS patients ( p  < 0.05). The SjS and HCQ groups differed in the I, R, SR, IL, and IR regions in the superficial and deep retina and the S region in the superficial retina. The ROC curves of the relationship between the HCs and SjS groups and between the SjS and HCQ groups demonstrated good classification accuracy. Conclusion: HCQ may contribute significantly to the microvascular alteration in SjS. Microvascular alteration is a potential marker with adjunctive diagnostic value. The MIR and the OCTA images of I, IR, and C1 regions showed high accuracy in minoring the alteration.